PENGARUH UKURAN PERUSAHAAN, TINGKAT HUTANG, DAN KESULITAN KEUANGAN TERHADAP KEPUTUSAN HEDGING PADA PERUSAHAAN MANUFAKTUR INDONESIA - Krisdian, Ni Putu Candra; Badjra, Ida Bagus (E-Jurnal Manajemen, 2017)
Hedging is undertaken by a company to protect the company from exposure to foreign currencies. Hedging decisions are influenced by firm size, debt level and financial distress. This study research the effect of firm size, debt level and the financial distress of the hedging decision using derivative instruments. This aim of this study to research the effect of each variable on the hedging decision using derivative instrument in manufacturing companies listed in Indonesia Stock Exchange in 2012 until 2015. Purposive sampling techniques are use to take sample, and appropriate criteria established company obtained 74 samples of manufacturing companies. Research on the effect of each variable on this hedging decisions using logistic regression analysis techniques. The results showed that each variable firm size, debt level and the financial distress has a positive and significant effect on hedging activities.
Keywords: hedging, firm size, debt level, financial distress